Nurses’ Knowledge Regarding Hospital Waste Management at a Specialized Hospital in Dhaka, Bangladesh - Bithy Gomes; Fahima Mahjabin; Fatema Gohora; Nasrin Aktar; Most. Sultana; Sarmin Akter; Khurshida Aktary; Shilpey Khatun; Kabita Barai; Mridula Baroi (American Journal of Nursing Science, 2026)
The hospital waste management have become a remarkable concern for the nurses and others health care personnel as it carries a higher risk of infection and injury. Hospital waste must be properly identified and disposed to selected point of origin as possible. To assess the level of nurses’ knowledge regarding hospital waste management at a specialized hospital in Dhaka. Methods: A descriptive type of cross-sectional study was conducted with 50 samples through convenient sampling technique from total number of populations at National Institute of Diseases of the Chest and Hospital (NIDCH), Dhaka, Bangladesh. A structured questionnaire was used for data collection and descriptive statistics was used for analysis. The mean age of the respondents was 35.5 years old. The overall findings showed that 30% of respondents had average knowledge, 28% of respondents had good knowledge, 26% of respondents had poor knowledge, 10% of respondents had very good knowledge and only 6% of respondents had excellent knowledge regarding hospital waste management. The study findings concluded that, the knowledge of nurses about management of hospital waste is crucial to ensure that such waste is managed properly. Finally, it is suggested to arrange in service training on hospital waste management to increase the level of nurses' knowledge regarding hospital waste management so that nurses can play a vital role in providing quality care to patients as well as save themselves from risk factors.